Bagaimana Kalimat Terbentuk? Kajian Teori Generatif-Transformatif dalam Pembelajaran Bahasa Arab - Intan Tri Ardhana; Julita Dwi Anggraeni; Rahadatul Aisyi; M. Yunus Abu Bakar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This article discusses how sentences are formed based on Generative-Transformational Theory and its application in Arabic language learning. The background of this article is rooted in the need to understand sentence formation not only as a Surface Structure but also as a mental process involving deeper linguistic mechanisms. The objective of this article is to describe the main ideas of the theory, including innate language ability , deep and Surface Structures, and Transformational Rules, as well as to explain its relevance in Arabic language instruction. This article employs a qualitative descriptive approach through literature review and conceptual analysis, supported by examples of sentence transformation in Arabic. The discussion highlights that language is a creative system governed by internal competence, where sentences are generated through a process from thought to deep structure, transformed into Surface Structure. The application in learning involves transformation exercises, structural analysis, and sentence variation practices. The findings indicate that this approach helps learners better understand sentence structure, produce sentences independently, and grasp the process of sentence formation more effectively. The implication of this article is that Arabic language teaching should emphasize understanding and cognitive processes rather than rote memorization.